SR ( Science and Religion ) SEBAGAI PENDEKATAN PEMBELAJARAN BIOLOGI PADA KURIKULUM 2013 UNTUK MENINGKATKAN KARAKTER SISWA - Nur Khasanah (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2016)
ABSTRACTThe learning activities is a process of discovery and experience so that the knowledge can improve students' understanding and the character. Science is often identified with the West. The Islamic education is often oriented to the future life tend to be defensive. Approach of Science and Religion (SR) is a combination of approaches concepts, process skills, inquiry, and discovery and approaches to religious values. The philosophy underlying the approach is a constructivist approach behavioristik SR, learners formulate their own concepts in cognitive structure based on their knowledge then implement the values that exist in the community surrounding and religious values. Subject of this research was a 45 students of MAN 1 Semarang academic year 2015-2016 Research was conducted in odd semester of 2015, include: 1) planning, 2) implementation, 3) observation,   and4) evaluation. The results showed a good indicator of student activity in the learning lab and discussions has been reached on the completeness of classical study on lab activities amounted to 82.44% with an average value of 81.48 liveliness, and discussions 81.86% with an average value of 82, 10 (criteria very well). Indicators student's character visits of religious attitudes, responsibility, honesty, respect, discipline, and self-contained. The conclusion were a. SR approach seeks to provide an understanding of How teach science by providing a vision of Islam in the classroom. b. SR approach applied to the learning process Biology can apply knowledge and improve the character of the students.